TELAAH KURIKULUM MERDEKA PADA JENJANG PENDIDIKAN DASAR ISLAM: ANALISIS FILOSOFI, STRUKTUR, DAN IMPLEMENTASI PROFIL PELAJAR PANCASILA - Restia Ananda Putri; Leni Rahmawati; Leni Rahmawati; Sartika Aulia; Hafizatul Ulya; Mey Hikna; Janiah Hernawati; Muammar; Ahmad Noviansah (Jurnal Cinta Nusantara (JCN), 2026)
The Merdeka Curriculum represents a fundamental transformation in Indonesia’s education system that emphasizes a student-centered learning approach, curriculum flexibility, and holistic development of competencies and character. This study aims to analyze the philosophy, structure, and direction of student development in the implementation of the Merdeka Curriculum at the Islamic basic education level, particularly in Madrasah Ibtidaiyah (MI). The method used is a literature review by examining various policy documents, scientific journals, textbooks, and relevant academic references. The results indicate that the Merdeka Curriculum is grounded in Ki Hajar Dewantara’s thoughts on learning freedom, constructivist paradigm, and humanistic approach. The curriculum structure consists of essential intracurricular learning and the Pancasila Student Profile Strengthening Project (P5) as a cross-disciplinary component. The Pancasila Student Profile with six dimensions serves as the main direction for shaping student character. Implementation of the Merdeka Curriculum in MI requires contextual adaptation that considers Islamic characteristics, teacher readiness, and infrastructure support. This study recommends strengthening teacher capacity, developing contextual teaching modules, and continuous evaluation for optimizing the implementation of the Merdeka Curriculum in Islamic basic education institutions